Functional evaluation of patients undergoing endoscopic calcaneoplasty for Haglund deformity - Bertelli, Hallan Douglas; Michelin, Bruno Arvatti; Perucci, Isabela Ferreira; Cillo, Mário Sérgio Paulillo de; Candido Castro Filho, Carlos Daniel; Huyer , Rodrigo Guimarães (Journal of the Foot & Ankle, 2021)
Objective: To analyze the functional outcomes of patients undergoing endoscopic calcaneoplasty for the treatment of Haglund deformity. Methods: This study consists of a case series of patients undergoing endoscopic calcaneoplasty. The American Orthopaedic Foot and Ankle Society ankle-hindfoot scale, was used to evaluate patients before and 12 months after the procedure, providing preoperative and postoperative scores. Results: Nineteen patients were evaluated for a total of 24 endoscopic calcaneoplasties. The American Orthopaedic Foot and Ankle Society scale provided a mean preoperative score of 31.4 and a mean postoperative score of 93.3, which shows a significantly increased score after surgery. The mean patient age was 52 years, and the youngest patient was 25 years old and the oldest patient was 73 years old. However, no significant relationship was found between age and change in the American Orthopaedic Foot and Ankle Society score. No complications were observed in the immediate or late postoperative periods. Conclusion: Arthroscopic resection is efficient in the treatment of Haglund deformity given the significant improvement in the American Orthopaedic Foot and Ankle Society score observed after the procedure. Also, no postoperative complications were seen in patients who underwent endoscopic calcaneoplasty. Level of Evidence: IV; Therapeutic Studies; Case series.